Architecture constructed notes on a discipline - Jarzombek, Mark (Bloomsbury Visual Arts, 2023)
"Archi-Tect explores the central, open secret of architecture: the long-suppressed conflict between arche and teckton-between those who design, and those who build. This unresolved tension has a centuries-old history in the discipline, persisting through Classical and Renaissance times to the present day, and yet it has rarely been addressed through a historical and theoretical lens. In this book, acclaimed architectural theorist Mark Jarzombek examines this tension head-on, and uses it to rethink the nature of the history of architecture. He reveals architecture to be a troubled, interconnected realm, incomplete and unstable, where labor, craft, and occupation are the 'invisible' complements to the work of the architect. Erudite, entertaining, and full of surprising and thought-provoking juxtapositions and challenges, Archi-Tect is packed with novel insights into the internal conflicts and paradoxes of architecture, and is rich with examples from modern and contemporary practice-including Mies, Koolhaas, Potrc, Hadid, Bawa, Diller + Scofidio-which demonstrate how contemporary architecture inhabits the very same tensions that have riven the discipline since the days of Alberti. This provocative book will stimulate conversations among students, researchers, and designers, as it pushes the boundaries on how we define the professional discipline of architecture and overturns entrenched assumptions about the nature of architectural history and theory"